Structural and Magnetic Properties of Nanocomposite Nd–Fe–B Prepared by Rapid Thermal Processing. (February 2020) - Yang, Jinbo; Han, Jingzhi; Tian, Haidong; Zha, Liang; Zhang, Xiongzuo; Song Kim, Chol; Liang, Dong; Yang, Wenyun; Liu, Shunquan; Wang, Changsheng
Abstract: Nanoscale permanent magnetic materials, which possess excellent magnetic and mechanical properties, thermal stability, and corrosion resistance, have become a research hotspot for permanent magnets. In reality, however, the obtained maximum energy product, ( BH )max, is not satisfactory in comparison with the theory limit, especially for exchange-coupled nanocomposite magnets. The construction of an ideal microstructure still remains a challenge in the synthesis and preparation of nanoscale permanent magnets. This work reported the impact of rapid thermal process (RTP) with electron-beam heating on the microstructures of Nd12.5- x Fe80.8+ x B6.2 Nb0.2 Ga0.3 ( x = 0, 2.5) nanocomposites. It was found that the crystallization time was greatly reduced, from 15 min under the conventional annealing conditions to 0.1 s under the RTP. For Nd2 Fe14 B single-phase materials, the crystallization temperature of the RTP ribbons decreased by about 248 °C compared with that of the ribbons produced by the conventional annealing method. A synergetic crystallization of the Nd2 Fe14 B and α-Fe phases was observed under the RTP, which restrained not only the shape, size distribution, and compositions of the hard and the soft phases, but also the interface between them. This modification effect became more obvious as the fraction of Fe increased. Due to the improvement in the uniformity of the Nd2 Fe14 B and α-Fe phases, and their grain size distribution, better magnetic properties were achieved using RTP in comparison with the conventional annealing method.